Structural unemployment in Europe: A bird's-eye view - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
This paper presents a synoptic interpretation of structural unemployment in Europe. The paper consists of three parts. Part 1 summarises some major stilysed facts of the record and the state of unemployment in Europe. In part 2, these facts are taken as the basis for a theoretical interpretation of the genesis and persistence of European unemployment. Part 3 contains policy conclusions. The main message of the paper is that the ultimate cause of European unemployment since the early 1980s is to be found in the path and pattern of structural change within an institutional framework that prevents a sufficient degree of structural wage flexibility to come about.
Keywords: J6; J60; J64; 330; Strukturelle Arbeitslosigkeit; Hysteresis; Arbeitsmarkt; Institutionalismus; Sozialstaat; Lohnrigidität; Europa